Tanggung Jawab Hukum Perusahaan Terhadap Hak Karyawan Dalam Program Dana Pensiun - Mustari Efendi; Wiradhika Wicaksono; Diana Ria W. Napitupulu (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The pension fund program or Pension Guarantee aims to maintain a decent standard of living for workers and their heirs by providing income after participants reach retirement age, experience permanent total disability or die. Pension Guarantee as a form of protection for workers in Indonesia that must be implemented by every employer or company. In principle, pension funds are one alternative to provide welfare guarantees to employees. This study aims to gain an understanding of employee rights in the pension guarantee program and the company's legal responsibility for employee rights in the pension fund program to improve worker welfare when they reach retirement age. The research uses a descriptive analytical research method that describes facts in the form of secondary data consisting of primary legal materials (legislation), secondary legal materials with a normative legal approach, namely a method that uses secondary data sources, namely laws and regulations, legal theories and opinions of scholars, which are then analyzed. Based on research, it was found that there are still workers or employees who are not registered for pension insurance by the Company. Pension insurance is an employee's right, so that not registering employees in a pension insurance program can cause legal protection problems for workers when they enter retirement age, experience permanent total disability or die. While on the other hand, companies that have intentionally or negligently not included employees in the pension insurance program can be held legally responsible either civilly or even criminally based on applicable laws and regulations.